PENGARUH GAYA HIDUP SEHAT DAN STRES PERAN TERHADAP HASIL KERJA AUDITOR (Studi Empiris pada Auditor yang Bekerja di KAP Semarang) - Pepin Nur Dhiansyah; Dul Mu’id (Diponegoro Journal of Accounting, 2015)
During busy season, auditors are usually confronted with excessive stress. Sometimes they have to work more than ten hours per day for several months. This condition will affect the result of work. This study aimed to examine the effect of healthy lifestyle role stress toward the job outcomes on auditors. The data of this study are collected through questionnaires completed directly by auditors who work in Public Accounting Firms in Semarang. The sample in this study was taken by using convenience sampling method. In analyzing technique, this study uses Structural Equation Modeling (SEM) analysis with the help of statistical program SmartPLS. The results of this study show that a healthy lifestyle mediated by the vitality cannot contribute significantly to the improvement of psychological well-being and eventually to the result of work on auditors.